Strategi Komunikasi Pemasaran melalui Digital Marketing Minyak Kayu Putih pada Kelompok Tani Hutan (KTH) Wonolestari, Desa Wonoharjo Boyolali - Sapja Anantanyu; Putri Permatasari; Joko Winarno; Suwarto Suwarto; Agung Wibowo (Universitas Muhammadiyah Semarang, 2022)
Eucalyptus is a type of productive plant in the forestry sector which has a fairly important role in the essential oil industry. Farmers of Wonoharjo Village, Kemusu District, Boyolali Regency cultivate eucalyptus plants and process them into eucalyptus oil products independently. Eucalyptus farmers in Wonoharjo Village are members of the Wonolestari 1 and Wonolestari 2 Forest Farmer Groups (KTH) who are still experiencing problems in carrying out a product marketing system, especially in the utilization of communication technology. Therefore, it is necessary to assist farmers in marketing eucalyptus oil products. The purpose of this community service activity is to provide education, assistance and training as an effort to increase the knowledge and skills of eucalyptus farmers in Wonoharjo Village in processing eucalyptus oil to have a high selling value by implementing online-based integrated marketing communications. The method of implementing service activities is carried out by preparing material handbooks, marketing socialization packaged through workshops, training, digital marketing communication practices with the preparatory and execution stages. The socialization activities carried out are able to increase the knowledge of eucalyptus oil farmers regarding digital marketing through several social media such as Instagram, Youtube and E-Commerce applications namely Shopee. Mentoring activities are expected to be able to increase product marketing by reaching consumers widely so that people's incomes also increase.